Attentional engagement and strategic responses to discontinuous environmental change: Evidence from the US banking industry - MACK, Daniel Z. (Institutional Knowledge at Singapore Management University, 2024)
While prior research has established a link between the attention an organization allocates to the external environment and its adaptations to environmental change, the nature of the cognitive processes that underlie this link remains underexamined. In this study, we explore how patterns of attentional engagement—that is, the extent to which attention allocation is focused and/or consistent over time—influence the organization’s formulation of strategic responses to discontinuous change. We advance a situated perspective on attentional engagement by suggesting how the type of learning and cognitive processes are situated in different attentional-engagement structures, and can, in turn, lead to heterogeneous strategic responses to the same discontinuous change. Specifically, we formulate a theoretical model elaborating how varied levels of attentional focus and attentional consistency affect whether organizations respond by breaking, reinforcing, hedging, or maintaining the status quo. Subsequently, we develop and test our arguments using a dataset covering U.S. banking firms from 2002 to 2010—a period that includes the U.S. housing crisis.